2020
DOI: 10.1186/s13054-020-2755-4
|View full text |Cite
|
Sign up to set email alerts
|

Facilitating ventilator weaning through rib fixation combined with video-assisted thoracoscopic surgery in severe blunt chest injury with acute respiratory failure

Abstract: Background: Severe blunt chest injury sometimes induces acute respiratory failure (ARF), requiring ventilator use. We aimed to evaluate the effect of performing rib fixation with the addition of video-assisted thoracoscopic surgery (VATS) on patients with ARF caused by blunt thoracic injury with ventilator dependence.Methods: This observational study prospectively enrolled patients with multiple bicortical rib fractures with hemothorax caused by severe blunt chest trauma. All patients received positive pressur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 28 publications
0
8
0
2
Order By: Relevance
“…One of the main goals after SSRF is pain reduction. In our previous study, SSRF dramatically reduced pain [ 15 , 16 ], and the analgesic dose was significantly reduced compared with patients who did not undergo SSRF. In this study, because all patients underwent SSRF, the analgesic dose was similar between both groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the main goals after SSRF is pain reduction. In our previous study, SSRF dramatically reduced pain [ 15 , 16 ], and the analgesic dose was significantly reduced compared with patients who did not undergo SSRF. In this study, because all patients underwent SSRF, the analgesic dose was similar between both groups.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical fixation was indicated for total displacement of fractured ribs. In our hospital, VATS is performed simultaneously with SSRF [ 15 , 16 ], and both procedures are arranged within days after trauma. General anesthesia with single-lung ventilation is also required during the operation.…”
Section: Methodsmentioning
confidence: 99%
“…This study also revealed that conducting SSRF in flail chest patients improved forced vital capacity (FVC), lung function, and cost-effectiveness; and ensured the quicker return of patients to fulltime work [ 32 ]. A 2020 observational study by Wu et al showed that ventilator-dependent patients with acute respiratory failure after severe blunt chest injury who underwent SSRF had shorter MVDs, HLOS, and pneumonia incidence [ 33 ].…”
Section: The Role Of Surgical Stabilisation Of Rib Fractures (Ssrf) I...mentioning
confidence: 99%
“…Die prozentuale Verteilung der Lungenverletzungen war für beide Gruppen identisch. Die Studie zeigt den hohen Anteil an intrathorakalen Begleitverletzungen bei Rippenserienfrakturen, sodass die Autoren aufgrund der Behandlungsvorteile für "VATS plus Rippenosteosynthese" das kombinierte operative Vorgehen empfehlen [41]. In mehreren Kohorten wird aufgrund der Detektion und thorakoskopischen Sanierung von intrathorakalen Begleitverletzungen sowie der Möglichkeit der Entlastung des retinierten Hämatothorax die Empfehlung zur Durchführung einer VATS im Rahmen der Thoraxwandosteosynthese gegeben [44,45,46].…”
Section: Thoraxchirurgie | üBersichtunclassified
“…Osteosynthesen der Thoraxwand werden offen, rein minimalinvasiv oder mit VATS-Unterstützung durchgeführt [37,38,40,41,42]. Während die rein minimalinvasive Versorgung von Rippenfrakturen noch in der Entwicklungsphase steht [43], ist zu klären, inwieweit die thorakoskopische Assistenz einen Vorteil bez.…”
Section: Empfehlungunclassified